IMPACT OF ENVIRONMENTAL AWARENESS ON UNDERGRADUATE COURSES: PERCEPTIONS OF BACHELOR'S DEGREE STUDENTS IN BUSINESS ADMINISTRATION ABOUT SELECTIVE WASTE COLLECTION AT FACELI (REMUNOM, 2024)
The growing concern with environmental degradation and the urgent need to adopt sustainable practices have fostered various global and local initiatives aimed at preserving the environment. In the academic context, higher education institutions play a crucial role in forming citizens who are aware and committed to sustainability. This paper aims to investigate the level of environmental awareness among students in the Bachelor of Administration program at the Faculdade de Ensino Superior de Linhares (FACELI) and their perception of the implementation of selective waste collection at the institution. The research adopted a quantitative and qualitative approach, using questionnaires to collect data from the students of the institution. The results showed that, although most students recognize the importance of selective waste collection and show a growing concern for environmental issues, it is still necessary to develop a more effective process of environmental education and awareness among the respondents. Therefore, for selective waste collection to become a consolidated practice at (FACELI), a joint effort between the administration, teachers, and students is needed to build an environmental culture.